Pengukuran Daya Ingat pada Lansia di posyandu Lansia - Wilda, Lexy Oktora; Tina, Pipit Ariani Agus (Universitas Nusantara PGRI Kediri, 2025)
Aging is a natural process in which a person experiences gradual physical, cognitive, and spiritual decline. One of the cognitive declines in the elderly is memory loss. The consequences of memory loss include forgetfulness, which, if left untreated, can lead to dementia. This community service project aimed to measure memory in the elderly. It was conducted at the Elderly Community Health Post (Posyandu) in Jambi Village, Baron District, Nganjuk Regency, involving 60 elderly people who were active in the Posyandu. The design used a cross-sectional approach, and data collection utilized the SMPSQ questionnaire. The data shows that of the 60 elderly, almost half, 27 elderly (45%) have moderate memory impairment, almost half, 17 elderly (28%) have good memory ability, and almost half, 16 elderly (27%) have mild memory impairment. This is influenced by gender, age, education, and occupation. Women are at greater risk of cognitive decline due to the role of the sex hormone estrogen, which is associated with low levels of estradiol in the body. Estradiol is thought to be neuroprotective, limiting damage from oxidative stress and protecting nerve cells from amyloid toxicity in Alzheimer's patients.